2010
DOI: 10.1007/s11096-010-9414-9
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in chronic illness management: a qualitative study of Australian pharmacists’ perspectives

Abstract: The identified incentives and barriers have provided valuable information on what pharmacists face in managing patients with chronic illness. Most of the solutions suggested by them have been tested and proven unsuccessful. Develop successful health policy to address the identified barriers remains a challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Similar results were found in a cross‐national assessment of patient and provider opinions of diabetes care in various countries that found that health‐care providers had difficulties to communicate with specialists . Another study showed that Australian pharmacists underlined communication problems between health‐care professionals and between professionals and patients . Our findings can be related to the solutions that participants suggested to motivate patients for self‐management.…”
Section: Discussionmentioning
confidence: 52%
“…Similar results were found in a cross‐national assessment of patient and provider opinions of diabetes care in various countries that found that health‐care providers had difficulties to communicate with specialists . Another study showed that Australian pharmacists underlined communication problems between health‐care professionals and between professionals and patients . Our findings can be related to the solutions that participants suggested to motivate patients for self‐management.…”
Section: Discussionmentioning
confidence: 52%
“…Twelve community pharmacists were used for this qualitative phase and saturation was deemed to be reached after approximately the 9 th interview as additional interviews did not present new concepts (Marshall & Rossman, 2010). This is similar to other qualitative investigations in pharmacy which have saturated near 12 interviews (Ferguson, Ashcroft, & Hassell, 2011;Kirking, 1984;Lehnbom & Brien, 2010). Subjects were licensed pharmacists in the study state in Johnson, Lynn, and Dubuque counties.…”
Section: Participants and Recruitmentsupporting
confidence: 70%
“…54 It has also been suggested that with sufficient infrastructure at the community pharmacy level, pharmacists' identification and resolution of drug-related problems could lead to improved patient outcomes and could also reduce health care costs, 55,56 with recognition that there are incentives and barriers to implementation of such activities. 57 However, even with the availability of clinical pharmacists at the community level for chronic disease management, there remains the issue of whether the patient can afford the medications.…”
Section: Discussionmentioning
confidence: 99%